Pandora's box - Saunders, Nick. (Milwaukee, WI : World Almanac Library, 2007)
Presents a graphic novel that tells the ancient Greek legend of Pandora and the chaos she unleashes when she opens up the mysterious box.
Includes bibliographical references (p. 47) and index.
3.1
5-8
Keywords: Pandora (Greek mythology) -- Comic books, strips, etc. -- Juvenile literature; Pandora (Greek mythology) -- Cartoons and comics; Mythology, Greek -- Cartoons and comics; Cartoons and comics; Pandora (Greek mythology) -- Comic books, strips, etc; Greek mythology -- Comic books, strips, etc; Comic books, strips, etc